Survival and response deepening after autologous transplantation in patients with multiple myeloma in Chile. Issue 1 (31st December 2022) - Guerra, María Carolina; Jerez, Joaquín; Godoy, Giselle; Briones, José Luis; Torres, Carlos; Hidalgo, Sebastián; Goldschmidt, Valentina; Gazitúa, Raimundo
ABSTRACT: Background: Autologous hematopoietic stem cell transplantation (ASCT) is the standard of care in candidate patients with newly diagnosed multiple myeloma. In Chile, its indication has been expanding as have centers dedicated to this type of therapy. Here, we present the results of the first 50 patients from a Chilean reference center. Methods: This was a retrospective analytical study of 50 patients referred to the Arturo López Pérez Foundation to receive ASCT. Patients newly diagnosed or on subsequent lines of treatment were allowed. As primary objectives, the deepening of response with ASCT and subsequent results on overall survival and progression-free survival were analyzed. Results: Among 50 patients with a median follow-up of 24 months, ASCT managed to deepen responses going from at least very good partial response of 57.4%–82.5% ( p = .01); complete response increased from 27.6% to 52.5% ( p = .02). In turn, a median progression-free survival (PFS) of 39 months was estimated and the median overall survival was not reached. The most important factor predicting PFS is measurable residual disease. Conclusions: ASCT is an effective strategy for prolonged progression-free survival and deepening responses. Public–private collaboration is a crucial element in reducing the gaps in access to this type of complex but highly effective therapy.